Diabetes associated with HPV infection in women aged over 50 years: A cross-sectional study from China’s largest academic woman’s hospital - Yue, Chaoyan; Zhang, Chunyi; Ying, Chunmei; Jiang, Hua (Frontiers in Endocrinology, 2022)
Background：Metabolic disturbances and immune alterations caused by diabetes are not just bystanders of HPV infection, but the conclusion that diabetes increases the risk of HPV infection requires more clinical epidemiological evidence to confirm. Our aim was to evaluate the association of diabetes with HPV infection risk in female patients aged over 50 years in the cervical clinic. Methods：We conducted a cross-sectional study of 6402 women aged over 50 years in the cervical clinic between May 2019 and March 2022 from China's largest academic woman's hospital. The quantitative-effect relationship between diabetes and HPV infection was observed by dose-response graph. Segmented multivariate logistic regression analysis was conducted to estimate the relative risk of HPV infection in diabetes patients. Multivariable predicted marginal proportions from logistic regression models were used to compute adjusted risk ratios. Results：There is a nonlinear relationship between HbA1c and the risk of HPV infection. When the HbA1c exceeds 5.7%, there is a saturation effect. After adjustment for confounders, the risk ratio for HPV infection in women with prediabetes was 1.09 (95% CI: 1.00-1.18) compared with women with HbA1c <5.7%, and the risk ratio for HPV infection in women with diabetes was 1.18 (95%). CI: 1.04-1.33). Sensitivity analysis showed that the risk ratio for HPV infection was 1.47 (95% CL: 1.07-1.91) when diabetes was associated with vaginitis. E-value analysis suggested robustness to unmeasured confounding. Conclusions：Diabetes and prediabetes are at increased risk of coinfection with HPV in female patients aged over 50 years in the cervical clinic.